Assessment of hydrothermal carbonization and coupling washing with torrefaction of bamboo sawdust for biofuels production. (June 2018) - Zhang, Shuping; Su, Yinhai; Xu, Dan; Zhu, Shuguang; Zhang, Houlei; Liu, Xinzhi
Graphical abstract: Highlights: Hydrothermal carbonization and coupling washing with torrefaction were evaluated. Biofuels with high fuel quality were generated from HTC and CWT processes. HTC and CWT processes both improved the combustion behavior of biofuels. Slagging and fouling index for biofuels after pretreatment was obviously improved. Abstract: Two kinds of biofuels were produced and compared from hydrothermal carbonization (HTC) and coupling washing with torrefaction (CWT) processes of bamboo sawdust in this study. The mass and energy yields, mass energy density, fuel properties, structural characterizations, combustion behavior and ash behavior during combustion process were investigated. Significant increases in the carbon contents resulted in the improvement of mass energy density and fuel properties of biofuels obtained. Both HTC and CWT improved the safety of the biofuels during the process of handling, storing and transportation. The ash-related issues of the biofuels were significantly mitigated and combustion behavior was remarkably improved after HTC and CWT processes of bamboo sawdust. In general, both HTC and CWT processes are suitable to produce biofuels with high fuel quality from bamboo sawdust.